Athenry Castle, south interior wall of hall, window jamb and arch moulding - O'Donovan, Danielle (My University, 2008)
Angle roll terminating the splay of the window jamb, moulding from angle comprises: roll, hollow, chamfer.
Window
Keywords: Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Medieval; roll moldings